The effect of combined use of chitosan and PIPS on push-out bond strength of root canal filling materials. Issue 18 (16th September 2016) - Aydin, Ugur; Aksoy, Fatih; Tosun, Samet; Ozsevik, Abdul Semih
Abstract: Adhesion of root canal filling materials to root dentin is important for the long-term success of the treatment. Push-out bond strength test is used to evaluate the adhesion capacity of root canal filling materials to root canal walls. The aim of the present study is to compare the bond strength of root canal filling materials to root dentin after irrigation with EDTA, chitosan and the combination of chitosan and PIPS irridation using push-out bond strength test. Forty-eight extracted teeth were resected until 13-mm long roots were obtained. Root canals were prepared with a size-25 OneShape instrument. Samples were divided into three groups each including 15 roots. Group 1: Canals were rinsed with 0.2% chitosan and subjected to laser irridation with PIPS at the same time. Group 2: Canals were rinsed with 0.2% chitosan. Group 3: Canals were rinsed with EDTA. All canals were filled with .06 tapered gutta-percha and AH-plus sealer. One-mm thick slices were taken from coronal, middle and apical one-thirds of the roots. Push-out bond strength was determined using a Universal Testing Machine. One root from each group was observed under SEM to evaluate the degree of smear removal. Statistical analysis was performed with Kruskall-Wallis test. Results showed that bond strength values were statistically similar in overall evaluation for all groups ( p > .05). In segmental evaluation, group 1 revealed the highest bond strength in apical one-third compared to other groups ( p < .05).